Fish and Fishery Products: Participation in the Demand for Nutrition from Animal Source to the People of Bangladesh (Bangladesh Journal of Nutrition, 2021)
Among different food items, fish/fishery product is the healthier one. For maintaining sound health and extending life span, along with fruits, vegetables, meat, fish/fishery products may contribute a lot. As a source of animal protein, healthy fat, vitamins, and minerals, fish is a very good option. The country has 0.29 million ha of inland closed (culture) water fisheries bodies along with littoral shrimp farms (National Fisheries Policy, 1998). It is also blessed with a territorial sea of more than 118,813 square km of area including 200 nautical miles (NM) of Exclusive Economic Zone (EEZ) with all kinds of living and non-living resources under the continental shelf up to 354 nautical miles from the Chittagong coast (MoFA,2014). Fish and other aquatic organisms from these water bodies are being caught for internal consumption as well as for export purposes. Mostly, this catch is sold as wet fish; some products are also prepared traditionally like dried, salted, and fermented. Smoked, canned, fish mince-based value-added products are not prepared yet on a commercial basis. For better utilization of the county’s catch and to contribute to the nutritional demand of the people it is necessary to take proper steps. Several academic and scientific institutes of the country are being engaged in developing fishery products and observing their storage possibilities. Here, findings of some researches performed on fish and fishery products in the Department of Fisheries Technology, Faculty of Fisheries, Bangladesh Agricultural University are discussed.Bangladesh J. Nutr. Vol. 34, December 2020, P: 99-108